Pengaruh Glass Ceiling Terhadap Pengembangan Karir di Moderasi oleh Budaya Organisasi dan Leader Member Exchange (Studi pada Aparatur Sipil Negara Perempuan Daerah Khusus Ibukota Jakarta) - Putra, Juniawan Mandala; Nurhayati, Mafizatun; Asih, Daru (Jurnal Doktor Manajemen (JDM), 2025)
This study aims to examine the influence of the glass ceiling on the career development of female civil servants in the Provincial Government of DKI Jakarta, while also assessing the moderating roles of organisational culture and Leader–Member Exchange (LMX). A quantitative method was employed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with a sample of 400 respondents selected through stratified random sampling. The findings reveal that the glass ceiling does not exert a significant effect on career development, whereas organisational culture and LMX demonstrate significant influences. Furthermore, organisational culture is found to be ineffective in moderating the relationship between the glass ceiling and career development, while LMX is shown to strengthen this relationship. These results underscore the critical importance of leader–subordinate relationships and a supportive organisational environment as key factors in overcoming structural barriers to women’s career progression in the public sector.